Are manual workers at higher risk of death than non-manual employees when living in Swedish municipalities with higher income inequality? - Henriksson, Göran; Allebeck, Peter; Weitoft, Gunilla Ringbäck; Thelle, Dag (European journal of public health, 2007)
Objectives: To test the hypothesis that manual workers are at higher risk of death than are non-manual employees when living in municipalities with higher income inequality. Design: Hierarchical regression was used for the analysis were individuals were nested within municipalities according to the 1990 Swedish census. The outcome was all-cause mortality 1992–1998. The income measure at the individual level was disposable family income weighted against composition of family; the income inequality measure used at the municipality level was the Gini coefficient. Participants: The study population consisted of 1 578 186 people aged 40–64 years in the 1990 Swedish census, who were being reported as unskilled or skilled manual workers, lower-, intermediate-, or high-level non-manual employees. Results: There was no significant association between income inequality at the municipality level and risk of death, but an expected gradient with unskilled manual workers having the highest risk and high-level non-manual employees having the lowest. However, in the interaction models the relative risk (RR) of death for high-level non-manual employees was decreasing with increasing income inequality (RR = 0.77; 95% CI, 0.63–0.93), whereas the corresponding risk for unskilled manual workers increased with increasing income inequality (RR = 1.24; 95% CI, 1.06–1.46). The RRs for skilled manual, low- and medium- level non-manual employees were not significant. Controlling for income at the individual level did not substantially alter these findings, neither did potential confounders at the municipality level. Conclusions: The findings suggest that there could be a differential impact from income inequality on risk of death, dependent on individuals' social position.